Análisis teórico del diseño instruccional desde el enfoque sistémico - Torres Lima, Héctor Jesús; Ramírez González, Carolina Ivette; Caldelas, Francisco (Mediaciones Sociales, 2007)
The study identified the organization of different instructional design models through the application of the systemic approach. Seven documents were analyzed in order to focus on the compulsory elements, to distinguish them and to relate them. Four key elements were identified: educational agents, techno-logical instruments, contents and process of teaching-learning. High quantities of optional elements were also found and the relations between the obligatory and supportive elements were classified. It was found that the analyzed models are of a procedural character and not theoretical. Each model presents undefinitions and confusions about what to understand, when, how and which elements should be used.
Keywords: Systems theory; Instructional design; Education; Technology; Latin America